Heuristics modelling for dynamic corporate performance assessment - Perumalsamy, Radhakrishnan; Natarajan, Jeyanthi (International Journal of Engineering and Technology, 2019)
A major goal of corporate performance is to maximize the shareholderâ€™s value. Corporate performance is evaluated with the help of EVA (Economic Value Added).EVA concept is employed to ascertain if the organization contributed positively to shareholderâ€™s wealth over a period of time. Efficient corporate performance management needs to capture the dynamic nature of the relevant factors occurring from multiple sources and when more number of Strategic Business Units(SBU) are involved , the complexity of the problem increases in the process. In this paper, an innovative heuristic methodology is proposed to generate necessary analytics to assess emerging corporate performance levels subject to the risk environment the company is operating in and to take appropriate mitigation measures to overcome inferior corporate performance.Â Â